Boundless Opportunities with Definite Limitations - Nikoletta Kaszás; Erzsébet Peter; Krisztina Keller; Tamás Kovács (DETUROPE)
In our comparative analyses we tried to identify those factors that can affect the success of the projects implemented at the border region. We involved three cross-border programs into our analyses and studied the project of the Austria-Hungary, Slovenia-Hungary and Hungary-Croatia Cross-border Co-operation Programmes. In this article we have undertaken to compare the results of these analyses and find out the similarities in the factors determining the project success. We assumed that there are no significant differences among the project success influencing factors in the studied programs, and the same or at least very similar affecting factors can determine the success. Our primary research proved this hypothesis, so thanks to it we can state that the projects implemented in the analysed cross-border cooperation programs are influenced by some organizational and individual factors: the time factor of the project success can be high if the project manager has direct management and monitoring rights and his or her authority does not depend on others; furthermore if the personality and the methodological competencies of the project manager are given. The project management success can be reached if the project manager has some managerial competencies, as well.